Ecocide of the Nechi river: Invocation of the inter communis effect - Restrepo Jimenez, Luis Carlos; Restrepo Londoño, Katheleen Johana; Restrepo Jimenez, Luis Carlos; Restrepo Londoño, Katheleen Johana; Restrepo Jimenez, Luis Carlos; Restrepo Londoño, Katheleen Johana (Corporación Universitaria Americana, 2024)
Introduction: Mining in Colombia has long been one of the economic activities carried out by the population, both illegally and artisanally; moreover, this practice hasspread to companies seeking to exploit these soil resources in our territories. However, the consequences of both practices raise alarms in nearby communities due to their damage to human health. Objective: The main objective of this work is to make the general public aware of the current situation of the Nechi River. This study employs a descriptive and qualitative approach to make visible the current situation of the Nechi River, affected by the indiscriminate use of harmful chemicals such as mercury and others, due to illegal mining practices. This approach allows for a detailed understanding of the environmental and health impacts on the communities surrounding the river.Reflection: The results indicated that the Nechi River is indeed undergoing an ecocide that has it on the brink of extinction. Conclusions: All the aforementioned obligesthe State authorities to act and prevent catastrophic results in the future, using legal tools such as invoking the inter comunis effect, which would allow, by extension, the recognition of rights to the Nechi River.